(untitled) (Orfeu, 2025)
This article examines one of Baden Powell’s most recurring groove patterns (levada), which is nicknamed “levada-tamborim” due to its resemblance to the tamborim’s samba practice. After revisiting the definition of groove as a circular pattern of repetition and variation, understanding how guitar grooves imitate percussion instruments, and observing tamborim practice in samba, we draw a parallel between the levada-tamborim and the idea of a time-line that permeates most of Afro-Brazilian music. Once the theoretical premises are defined, we approach this groove type by examining five examples taken from recordings and videos by Baden and Marcel Powell. Our analysis reveals many ways of realizing the levada-tamborim, which, nonetheless, understand the guitarist’s right-hand action as integrated by two complementary groups whose action mirrors the non-stop rhythm of the samba groove played by the tamborim.